Respuesta :
Answer:
First problem: Solving for g.
[tex]g=27^{\frac{1}{x-2}}[/tex]
Second problem: Solving for x.
[tex]x=\log_g(27)+2[/tex]
Third problem: Assuming g is 9 while solving for x.
[tex]x=3.5[/tex]
Step-by-step explanation:
First problem: Solving for g.
[tex]g^{x-2}=27[/tex]
Raise both sides by 1/(x-2).
[tex](g^{x-2})^{\frac{1}{x-2}}=27^{\frac{1}{x-2}}[/tex]
[tex]g^{1}=27^{\frac{1}{x-2}}[/tex]
[tex]g=27^{\frac{1}{x-2}}[/tex]
Second problem: Solving for x.
[tex]g^{x-2}=27[/tex]
x is in the exponent so we have to convert to logarithm form since we desire to solve for it:
[tex]\log_g(27)=x-2[/tex]
Add 2 on both sides:
[tex]\log_g(27)+2=x[/tex]
[tex]x=\log_g(27)+2[/tex]
Third problem: Assuming g is 9 while solving for x.
[tex]9^{x-2}=27[/tex]
I'm going to solve this in a different way than I did above but you could solve it exactly the way I did for x when 9 was g.
I'm going to write both 9 and 27 as 3 to some power.
9=3^2 while 27=3^3.
[tex](3^2)^{x-2}=3^3[/tex]
[tex]3^{2x-4}=3^3[/tex]
Since both bases are the same on both sides, we need the exponents to be the same:
[tex]2x-4=3[/tex]
Add 4 on both sides:
[tex]2x=7[/tex]
Divide both sides by 2:
[tex]x=\frac{7}{2}[/tex]
[tex]x=3.5[/tex]
Now earlier for x in terms of g we got:
[tex]x=\log_g(27)+2[/tex]
I we input 9 in place of g and put it into our calculator or use some tricks without the calculator to compute we should get 3.5 as the answer like we did above when g was 9.
[tex]x=\log_9(27)+2[/tex]
[tex]x=\frac{3}{2}+2[/tex]
[tex]x=1.5+2[/tex]
[tex]x=3.5[/tex]